Public stock management - Disamwalla, Ammar (International Food Policy Research Institute, 1988)
Governments in developing countries have traditionally played a dominant role in foodgrain supply management. The problems and issues raised by this intervention have been analyzed in a number of studies made during the last decade. An understanding of the role that stocks can play for a commodity can be obtained from the following simple identity between aggregate supply and demand.